UV/IR phenomenon of Noncommutative Quantum Fields in Example - Hung, Nguyen Quang; Tu, Bui Quang (VNU Journal of Science: Mathematics - Physics; Vol 31 No 1, 2015)
Noncommutative Quantum Field (NCQF) is a field defined over a space endowed with a noncommutative structure. In the last decade, the theory of NCQF has been studied intensively, and many qualitatively new phenomena have been discovered. In this article we study one of these phenomena known as UV/IR mixing. Keywords: Noncommutative quantum field theory.